Presentation of "Sensitivity Analysis for Linear Systems based on Reachability Sets" - Silvestre, Daniel (2020)
Over-parameterized models - a complex systems can have simpler models if possible to measure their effect on the state or output. Multi-agent systems - there are local dynamics coupled by a network and identifying nodes with the most impact is cumbersome. Worst-case effect - proposed solution should look at bad trajectories.